2000
DOI: 10.1099/0022-1317-81-2-401
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial distribution and function in herpes simplex virus-infected cells

Abstract: In this study, mitochondria migrated to a perinuclear region in the cytoplasm in herpes simplex virus (HSV)-infected cells. HSV infection did not promote the expression of cytochrome c oxidase subunit 2 but did promote that of stress-responsive HSP60, both of which are known to be components of mitochondria. The levels of cellular ATP and lactate and mitochondrial membrane potential were maintained for at least 6 h but decreased at the late stage of infection. It was also found that the UL41 and UL46 gene prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 23 publications
14
91
0
Order By: Relevance
“…21 A similar redistribution of mitochondria around the nucleus of infected neurons was demonstrated in the case of HSV infection accompanied by increased concentration of viral tegument proteins around the nucleus. 34 Interestingly, such a perinuclear clustering of mitochondria was also observed in fibroblasts obtained from Alzheimer's patients, suggestive of a relevance to neurodegenerative conditions. 35 We wanted to determine whether TC-83 infection led to alterations in the distribution of mitochondria in infected cells.…”
Section: Mitochondrial Distribution Is Altered In Tc-83 Infected U87mmentioning
confidence: 84%
“…21 A similar redistribution of mitochondria around the nucleus of infected neurons was demonstrated in the case of HSV infection accompanied by increased concentration of viral tegument proteins around the nucleus. 34 Interestingly, such a perinuclear clustering of mitochondria was also observed in fibroblasts obtained from Alzheimer's patients, suggestive of a relevance to neurodegenerative conditions. 35 We wanted to determine whether TC-83 infection led to alterations in the distribution of mitochondria in infected cells.…”
Section: Mitochondrial Distribution Is Altered In Tc-83 Infected U87mmentioning
confidence: 84%
“…In addition to this accepted marker of mitochondrial stress, maintenance of the mitochondrial membrane potential (MMP) is also utilized as a marker of mitochondrial function [17,18,24,38]. We have shown that these two events correlate with increased mitochondrial fission and mitophagy, contributing to cell death in an infection dependent manner [24].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, significantly morphological changes of mitochondria also appear in the RGV-infected fish cells, and numerous dumbbell-shaped mitochondria are distributed around the viromatrix. Previous reports have indicated that changes of the mitochondrial distribution not only provide the energy for virus pathogenesis, but also play important roles in the process of apoptosis [26,27]. In the cases of the mammalian viruses, mitochondrial distribution changes and apoptosis occurrence have been observed during viral infection [28,29].…”
Section: Discussionmentioning
confidence: 99%